Mitogenic effects of a mesothelial cell growth factor: evidence for a potential autocrine regulation of normal and malignant mesothelial cell proliferation. - Donna, A. (1992)
We have investigated the growth-factor-like activity of a approximately 200-kDa, IP 8.3, cytoplasmic glycoprotein, the expression of which appears to be restricted to normal and malignant human mesothelium. This substance stimulated the growth of human mesothelioma cell cultures at greater rates than did foetal calf serum, but it failed to induce proliferation of lung carcinoma cell cultures. In addition, we have tried to trace the biosynthetic pathway of this mitogenic factor in normal human mesothelial cells by means of immuno-electron microscopy with a polyclonal antibody directed against this molecule. Positive immunogold labelling was found in the lumina of the cisternae of the endoplasmic reticulum, to a lesser extent on the outer surface of the plasma membrane, and also in structures corresponding to the coated pits. These ultrastructural findings are consistent with the hypothesis of the glycosylation of the newly synthesized protein in the endoplasmic reticulum and the subsequent uptake of the secreted molecule, which accumulates in the coated pits before internalization. The results suggest that this mitogenic glycoprotein could play a role in an autocrine growth control mechanism influencing mesothelial cell proliferation.